Analisis Dan Perancangan Sistem Electronik Medical Record (Emr) Pada Rumah Sakit Umum Daerah H. Abdul Manap Kota Jambi - Ahmad Yani; Marthiawati, Noneng; Ediansa, Oka (LPPM Universitas Adiwangsa Jambi, 2023)
Hospitals have the function and purpose of health service facilities which carry out service activities in the form of outpatient services, inpatient services, emergency services, referral services which include medical record services and medical support and are used for education, training and research for health workers. Medical record is written evidence regarding the service process provided to patients by doctors and other health workers, where with this written evidence, the medical record provided can be accounted for, with the aim of supporting orderly administration in efforts to improve medical record health services. The H. Abdul Manap Regional General Hospital, Jambi City, has implemented a medical record information system in its patient data collection service process, but it is still not integrated in terms of patient data collection from registration to medical records. The methodology used in designing this information system uses the UML (Unified Modeling Language) Model. This methodology can be used to analyze and design a medical record information system for the H. Abdul Manap Regional General Hospital, Jambi City, so that the results of this medical record information system can help overcome existing problems and no more recording data repeatedly and when data is needed can be seen immediately